Relationship between swimming speed and trunk muscle activity in crawl swimming - Hyodo, H.; Koga, D.; Sengoku, Y.; Wada, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION In crawl swimming, rotational movement around the long axis of the trunk is performed in conjunction with the stroke movement of the upper limbs, and this movement is defined as trunk rotation movement. In crawl swimming, since the upper and lower limbs are moved alternately, contraction and control of the trunk muscles are important [1]. It has been reported that the timing of switching the torsion motion of the knee shifts to an early stage [2]. The purpose of this study was to clarify the trunk muscle activation with changes in swimming speed during crawl swimming and to investigate the relationship with trunk twisting movements.